Standard dose Cytarabine-Induced Encephalopathy in an Acute Myeloid Leukemia Patient: A Case Report - Mehrshad Ebrahimpour; Samin Ghorbani Moghadam; Mostafa Kamandi; Omid Arasteh (Research Center for Rational Use of Drugs (RCRUD), 2024)
The mainstay of treatment for acute myeloid leukemia (AML), cytarabine, is known to induce encephalopathy, usually at high doses. During induction chemotherapy, a 38-year-old woman with non-M3 AML experienced encephalopathy following the administration of standard-dose cytarabine. The patient's mental state deteriorated, and she exhibited symptoms of physical weakness, confusion, and lethargy. There were no abnormalities in the brain parenchyma discovered by a CT scan. After a diagnosis of cytarabine-induced encephalopathy, cytarabine treatment was abruptly discontinued. Levetiracetam was used for managing seizures, intravenous hydration, and medication management, all of which were put into place as supportive measures. Over the next few days, the patient's mental state got better, and ten days later, she was fully conscious again. The encephalopathy and cytarabine were likely related, according to the Naranjo scale. Cytarabine was not reintroduced due to the patient's recovery and to prevent any potential problems. Rather, an alternate treatment regimen consisting of etoposide and mitoxantrone was initiated. This case emphasizes how crucial it is to take cytarabine-induced encephalopathy into account as a possible side effect when treating AML, even at lower doses of the medication. to minimize patient morbidity and ensure a successful treatment course, healthcare practitioners need to be on alert for signs and symptoms of this condition. Early detection and rapid cessation of cytarabine medication are critical steps in this regard.